A comparative taphonomic study of tooth marks caused by Iberian wolves (Canis lupus signatus) and domestic hunting dogs (Rehala) (Canis familiaris) on bovine scapulae, for taxonomic differentiation - Toledo González, Victor Antonio; Pérez Lloret, Pilar; Navarro Cáceres, Pablo; Chamorro Sancho, Manuel José; Ortega Ojeda, Fernando Ernesto; García Ruiz, Carmen; Krešimir, Severin; Fonseca Platini, Gabriel (Applied Animal Behaviour Science, 2023)
For many years, the conflict between humans and wolves has persisted due to the death of livestock attributed to the attack of these animals and dogs, causing high economic costs to owners and governments. To remedy this problem, differential compensation programs have been established for the affected owners, depending on the attacker. Obtaining these benefits requires evidence to demonstrate the veracity of the complaint. Reliable approaches are needed nowadays to detect the predator, beyond any reasonable doubt. Although the analysis of teeth marks on bones has been used to differentiate carnivores, especially for archaeological purposes, its interpretation for forensic purposes is still ambiguous, due to the high range of factors that can influence tooth mark patterns, and it has scarcely been considered in previous work. This study analyzed and compared the tooth marks caused by captive Iberian wolves and by a group of domestic hunting dogs (rehala) on fresh, and disarticulated (isolated) bovine scapulae, for taxonomic differentiation purposes. Wolves showed a higher rate of modification throughout the study and, although tooth marks caused by wolves tend to be larger and wider than those caused by dogs, in most cases it was possible to find overlap between the two subspecies. Bone modifications are conditioned by a number of factors intrinsic to the scavenger or predator species, and intrinsic to the aggressor and the environment, that must be considered during the interpretation of tooth marks found on bones at a crime scene. Along with the comprehensive analysis of all evidence, the analysis of new variables of tooth marks on bones, using novel image processing methodologies and statistical analysis, has shown high potential to identify the morphological and/or morphometric variables that allow taxonomic differentiation